The REM sleep behavior disorder screening questionnaire-A new diagnostic instrument - Stiasny-Kolster, Karin; Mayer, Geert; Schäfer, Sylvia; Möller, Jens Carsten; Heinzel-Gutenbrunner, Monika; Oertel, Wolfgang H. (Movement disorders, 2007)
Many patients with assumed idiopathic REM sleep behavior disorder (RBD) may actually represent an early clinical manifestation of an evolving neurodegenerative disorder, such as the α‐synucleinopathies, Parkinson's disease or multiple system atrophy. Early detection of these patients is clinically relevant for long‐term prospective as well as future neuroprotective studies. For this purpose, we validated a 10‐item patient self‐rating questionnaire (maximum total score 13 points) covering the clinical features of RBD. The RBD screening questionnaire (RBDSQ) was applied to 54 patients with polysomnographically confirmed RBD (29 men; mean age 53.7 ± 15.8 years), 160 control subjects (81 men; mean age 50.8 ± 15.5 years) in whom RBD was excluded by history and polysomnography (PSG, control group 1) and 133 unselected healthy subjects (58 men; mean age 46.9 ± 12.3 years; no PSG, control group 2). In most subjects (n = 153) of control group 1, other sleep‐wake disturbances were present. The mean RBDSQ score in the RBD group was 9.5 ± 2.8 points compared with 4.6 ± 3.0 points in control group 1 (P < 0.0001). Considering an RBDSQ score of five points as a positive test result, we found a sensitivity of 0.96 and a specificity of 0.56. The RBDSQ poorly discriminated patients with the most challenging differential diagnoses such as sleepwalking or epilepsy. In control group 2, the mean RBDSQ score (2.02 ± 1.78) was significantly lower than in the RBD group (P < 0.0005), revealing a specificity of 0.92. Due to its high sensitivity, the RBDSQ appears to be particularly useful as a screening tool. © 2007 Movement Disorder Society